Análisis subléxico del verbo de movimiento "Pasear" - Valdés-León, Gabriel (2019)
This paper presents a study that aimed to propose a minimal definition of the verb “pasear” as a verb of movement through the combinatorial analysis with nouns of complex delimitation, namely as montaña-monte and mar-océano. For this, we propose, first of all, a theoretical framework that considers the main ideas of the Generative Lexicon Theory (GLT) and a review of the most relevant studies regarding the verb “pasear” as a movement verb, to make way for an analysis combinatorial made from the appearances in the CORPES XXI. Later, these results are related, of lexicological nature, with possible lexicographical applications in some cases of difficult delimitation. Within the main results, this work proposes a definition of the verb “pasear” that considers the inclusion of the [± recreational] feature as part of the qualia structure, which could contribute not only with the establishment of limits in entries that have diffuse border lines, but also inthe studies of lexical and compositional semantics.